2017
DOI: 10.2174/1574888x12666170829161058
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Mechanism of Hair Growth Stimulation by Adipose-derived Stem Cells and Their Secretory Factors

Abstract: ADSC-CM promotes hair growth in vitro, ex vivo, and in vivo. Given that ADSCs are one of the most accessible sources of MSCs, ADSC-derived proteins may be feasible clinical therapeutic agents for the treatment of hair loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 0 publications
3
43
0
Order By: Relevance
“…Localized supplementation of growth factors and cytokines favoring hair growth was reported to promote hair regeneration [8]. Previous reports show that ADSC-CM promoted hair growth by regulating the cell cycle and inducing the anagen phase of the hair cycle, thereby promoting the proliferation of DPCs and possibly epithelial cells [9]. Our current results are consistent with those findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Localized supplementation of growth factors and cytokines favoring hair growth was reported to promote hair regeneration [8]. Previous reports show that ADSC-CM promoted hair growth by regulating the cell cycle and inducing the anagen phase of the hair cycle, thereby promoting the proliferation of DPCs and possibly epithelial cells [9]. Our current results are consistent with those findings.…”
Section: Discussionsupporting
confidence: 91%
“…ADSCs-CM has been reported to be rich in growth factors and cytokines, including vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), platelet-derived growth factor (PDGF), hepatocyte growth factor (HGF), keratinocyte growth factor (KGF), and insulin-like growth factor I (IGF-I) [8]. These growth factors and cytokines potentially modulate the host environment and thereby play significant roles in hair growth [9]. Previous studies found that human hair regrowth and density increased significantly after the application of ADSCs-CM [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…While our pilot study suggests that transplanted nestin + cells stimulate keratinocyte migration, the underlying mechanism is unclear. However, given that mesenchymal stem cells are well known for their extensive repertoire of secretory activities [ 8 , 19 , 20 ], it is conceivable that nestin + progenitor cells, which may be comparable in their highly plastic differentiation potential to adipose-derived mesenchymal stem cells, also impact on keratinocyte migration by secreting migration-enhancing growth factors. Clearly, future studies will have to determine how nestin + cells influence the balance between keratinocyte proliferation, apoptosis, migration and differentiation, culminating in the acceleration of epidermal repair.…”
Section: Discussionmentioning
confidence: 99%
“…AGA is characterized by shortening of the anagen phase and prolongation of the telogen phase, resulting in HF miniaturization in androgen-sensitive scalp and conversion into vellus hair [7]. Thus, the majority of prospective therapeutic strategies for AGA treatment involve the modulation of hair cycle dynamics, specifically prolonging or inducing the anagen phase [8,9]. The present article focuses on the current methods used to evaluate the hair growth-promoting effects of candidate substances, providing a useful overview of published hair growth evaluation assays in cells, organs, and animal models (Table 1 and Fig.…”
Section: Introductionmentioning
confidence: 99%